2022
DOI: 10.1038/s41396-022-01232-9
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and genomic responses of soil microbiomes to high-severity wildfire: linking community assembly to functional potential

Abstract: Increasing wildfire severity, which is common throughout the western United States, can have deleterious effects on plant regeneration and large impacts on carbon (C) and nitrogen (N) cycling rates. Soil microbes are pivotal in facilitating these elemental cycles, so understanding the impact of increasing fire severity on soil microbial communities is critical. Here, we assess the long-term impact of high-severity fires on the soil microbiome. We find that high-severity wildfires result in a multi-decadal (>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 84 publications
2
36
2
Order By: Relevance
“…So far, two studies have applied gene-resolved metagenomic analyses to post-fire soils 23,33 . Genome-resolved metagenomic tools can link potential pyrophilous traits (for example, fast growth rate, heat resistance) to specific organisms that thrive in burned soils and support laboratory observations 34 . Furthermore, this approach enables a broader understanding of microbiome function through identification of co-occurring functional traits, potential interspecies interactions, and viral-host dynamics.…”
mentioning
confidence: 99%
“…So far, two studies have applied gene-resolved metagenomic analyses to post-fire soils 23,33 . Genome-resolved metagenomic tools can link potential pyrophilous traits (for example, fast growth rate, heat resistance) to specific organisms that thrive in burned soils and support laboratory observations 34 . Furthermore, this approach enables a broader understanding of microbiome function through identification of co-occurring functional traits, potential interspecies interactions, and viral-host dynamics.…”
mentioning
confidence: 99%
“…To analyze the diversity of different gene categories (e.g., CAZy, nitrogen and sulfur cycling genes), Shannon index was calculated using diversity function in R package of “vegan” ( Oksanen et al, 2020 ). For each sample, the gene counts were normalized to the total number of amino acid coding gene sequences predicted by Prodigal prior to downstream analysis ( McKnight et al, 2019 ; Dove et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted April 10, 2023. ; https://doi.org/10.1101/2023.04. 10.536191 doi: bioRxiv preprint carbon turnover (22,25,26,27), however, this is yet to be established in fire-affected tropical peatlands.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to effects on microbiome diversity and composition, fires affect the predictability of microbiome compositional shifts by altering the relative balance between deterministic and stochastic assembly processes. A limited number of studies on mineral soil ecosystems have shown that the predictability of microbiome shifts post-fire depends on time since fire (27,28,29). An increase in stochastic processes such as dispersal and ecological drift was observed for a brief period (4-16 weeks) post-fire likely due to limited competition and weak environmental cues (28).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation